PERFORMANCE ANALYSIS OF AGRICULTURAL EXTENSION ON HORTICULTURE CROPS PRODUCTION TOWARDS SUSTAINABLE AGRICULTURE IN BATU CITY - widiyawati, Nurul; Arvianti, Eri Yusnita; Santosa, T. Budi (Universitas Veteran Bangun Nusantara, 2025)
This research aims to determine how much influence the role of agricultural instructors as motivator, supervision, timeliness and effectiveness has on horticultural crop production in Batu City, to determine the role and performance of agricultural instructors in the context of horticultural crop production in Batu City, and to determine the impact felt by farmers from the performance of agricultural instructors in horticultural crop production towards sustainable agriculture in Batu City. The research results show that service performance with quality and quantity has a significant effect on crop production as proven by the results of the T test with a P value = 0.000. Extension agents as supervisors do not have a significant effect on plant products. This is proven by the P value in the T test = 0.063. Extension agents as timeliness have a significant effect on plant products as evidenced by the P value in the T test = 0.001. Extension agents as effectiveness have no effect on plant products. This is proven by the P value in the T test = 0.170. The influence of service performance on quality and quantity, instructors as supervision, instructors as timeliness and instructors as effectiveness simultaneously have a significant effect on plant products. This is proven by the P value in the F test results = 0.000 and the level of relationship based on the R2 test = 0.710 or 71.0%. Keywords: Performance, Extension, Horticultural Crops, Sustainable Agriculture